Improved Accuracy In Bandwidth Estimation Based On Slops Methodology - Amil, Mazni (2010)
An increase consumption of bandwidth by networked application has been created the urge to have a measurement tool which is used to measure the available bandwidth, in order to maximize the usage of this limited resource.